2007
DOI: 10.1103/physrevb.75.085203
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Mn-implanted Si

Abstract: Structural and ferromagnetic properties in Mn implanted, p-type Si were investigated. High resolution structural analysis techniques like synchrotron X-ray diffraction revealed the formation of MnSi 1.7 nanoparticles already in the as implanted samples. Depending on the Mn-fluence, the size increases from 5 nm to 20 nm upon rapid thermal annealing. No significant evidence is found for Mn substituting Si sites either in the as-implanted or annealed samples. The observed ferromagnetism yields a saturation moment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
99
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 28 publications
(33 reference statements)
5
99
0
Order By: Relevance
“…2,3, 12,13,16 In that respect, a detailed study of the lattice sites occupied by implanted Mn in the phase-pure regime (dilute, randomly distributed Mn) should clarify whether this is indeed the case. We have addressed these questions by applying the electron emission channeling technique (EC) from implanted radioactive 56 Mn probes to different doping types of Si single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…2,3, 12,13,16 In that respect, a detailed study of the lattice sites occupied by implanted Mn in the phase-pure regime (dilute, randomly distributed Mn) should clarify whether this is indeed the case. We have addressed these questions by applying the electron emission channeling technique (EC) from implanted radioactive 56 Mn probes to different doping types of Si single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetic ordering in silicon implanted with Mn + ions (Si:Mn) has been reported recently; this ordering is evidently related to the structure of Mn-enriched near-surface layer in the implanted material [8]. It has been found that, for Si:Mn produced by implantation with Mn + doses, D = 10 15 -10 16 cm -2 , at energy, E = 300 keV, Curie temperature exceeds 400 K after rapid thermal annealing at 1070 K. Ferromagnetic properties of Si:Mn have been attributed to formation of MnSi 1.7 [9]. As it has been stated earlier [10,11], not only temperature but also enhanced hydrostatic pressure of ambient (HP) at processing of Si:Mn affect its structural and magnetic properties.…”
Section: Introductionmentioning
confidence: 91%
“…Ferromagnetic ordering in silicon implanted with Mn + ions (Si:Mn) has been reported recently; this ordering is evidently related to the structure of Mn-enriched near-surface layer in the implanted material [8]. It has been found that, for Si:Mn produced by implantation with Mn , at energy, E = 300 keV, Curie temperature exceeds 400 K after rapid thermal annealing at 1070 K. Ferromagnetic properties of Si:Mn have been attributed to formation of MnSi 1.7 [9]. As it has been stated earlier [10,11], not only temperature but also enhanced hydrostatic pressure of ambient (HP) at processing of Si:Mn affect its structural and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%